Restoration of Elbow Flexion in Traumatic Upper Brachial Plexus Palsy in Adults: Outcome with Intraplexus Distal Nerve Transfers in 78 Patients - Siqueira, Mario G.; Martins, Roberto S.; Faglioni Junior, Wilson; Foroni, Luciano; Heise, Carlos Otto (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Objective To present the functional outcomes of distal nerve transfer techniques for restoration of elbow flexion after upper brachial plexus injury.Method The files of 78 adult patients with C5, C6, ± C7 lesions were reviewed. The attempt to restore elbow flexion was made by intraplexus distal nerve transfers using a fascicle of the ulnar nerve (group A, n = 43), or a fascicle of the median nerve (group B, n = 16) or a combination of both (group C, n = 19). The result of the treatment was defined based on the British Medical Research Council grading system: muscle strength < M3 was considered a poor result.Results The global incidence of good/excellent results with these nerve transfers was 80.7%, and for different surgical techniques (groups A, B, C), it was 86%, 56.2% and 100% respectively. Patients submitted to ulnar nerve transfer or double transfer (ulnar + median fascicles transfer) had a better outcome than those submitted to median nerve transfer alone (p < 0.05). There was no significant difference between the outcome of ulnar transfer and double transfer.Conclusion In cases of traumatic injury of the upper brachial plexus, good and excelent results in the restoration of elbow flexion can be obtained using distal nerve transfers.
Keywords: brachial plexus palsy; distal nerve transfers; elbow flexion restoration